Exploring Subcultural Trajectories: Racist Skinhead Disengagement, Desistance, and Countercultural Value Persistence. Issue 3 (2nd July 2020) - Madfis, Eric; Vysotsky, Stanislav
ABSTRACT: This study analyzes the life histories and subcultural trajectories of people who have at one time but no longer identify as racist skinheads. We find that, on the one hand, people are far more malleable with their subcultural identities than is commonly understood by law enforcement and researchers concerned with criminal desistance, and on the other hand, this does not necessitate a total abdication of stable subcultural identities and values as some recent post-subculture scholars have asserted. Accordingly, we conceptualize the phenomena of subcultural trajectories and discuss the implications of these findings for future scholarship on subcultural participation and desistance as well as for potential public policies to successfully fight racism.